COMPARISON OF THE ABILITY OF MATHEMATICAL REASONING OF SMK STUDENTS USING A METACOGNITIVE SKILL APPROACH THROUGH ADVANCE ORGANIZER LEARNING MODELS WITH A SAINTIFIC APPROACH THROUGH DISCOVERY LEARNING - Rolina, Rosalina; Aryani, Sri; Taufiqurrohman, Erik ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2018)
This research is motivated by the low level of mathematical reasoning ability students. This study aims to determine the comparison of mathematical reasoning abilities students between those who learn using the metacognitive skills approach through advance organizer and the scientific approach through discovery learning. The method is an experimental method with a pretest-posttest control group design involving two groups and random sampling. At the beginning and end of learning, the two classes are given a test. The population in this study were State Vocational High School students in Cimahi, while the sample consisted of two randomly selected classes. Obtained class XI TEK A  which was given a metacognitive skill approach through advanced organizer and class XI TOI A  is given a scientific approach through discovery learning. The instrument used was a 5-item mathematical reasoning ability test description, then the data mathematical reasoning students were analyzed with descriptive and inferential statistics using the help of SPSS 21 software. Based on the results of the study, it was concluded that the improvement of students' mathematical reasoning using skills the metacognitive skills approach through advance organizer is better than students who use a scientific approach through discovery learning.